The influences of static and interactive dynamic facial stimuli on visual strategies in persons with Asperger syndrome - Falkmer, M.; Bjallmark, A.; Larsson, M.; Falkmer, Torbjorn (Elsevier Inc., 2010)
Several studies, using eye tracking methodology, suggest that different visual strategies in persons with autism spectrum conditions, compared with controls, are applied when viewing facial stimuli. Most eye tracking studies are, however, made in laboratory settings with either static (photos) or non-interactive dynamic stimuli, such as video clips. Whether or not these results are transferable to a “real world” dialogue situation remains unclear. In order to examine the consistency of visual strategies across conditions, a comparison of two static conditions and an interactive dynamic “real world” condition, in 15 adults with Asperger syndrome and 15 matched controls, was made using an eye tracker. The static stimuli consisted of colour photos of faces, while a dialogue between the participants and the test leader created the interactive dynamic condition. A within-group comparison showed that people with AS, and their matched controls, displayed a high degree of stability in visual strategies when viewing faces, regardless of the facial stimuli being static or real, as in the interactive dynamic condition. The consistency in visual strategies within the participants suggests that results from studies with static facial stimuli provide important information on individual visual strategies that may be generalized to “real world” situations.Consistency across conditions; Eye tracking; Facial stimuli; Fixation durations; Number of fixations